La comunicación online de la RSC en materia medioambiental. El caso de empresas de moda rápida y moda lenta - Laura GARCÍA-HUGUET (Fonseca, Journal of Communication, 2023)
Citizens’ concern about the environmental impact of their actions has led them to rethink their consumption habits towards more sustainable ones regarding their environment. Companies, as social entities and both for this reason and for their environmental, social and economic impact, have to rethink their business strategy towards a more sustainable one which is more committed to these three spheres in a business paradigm in which the correct management of the intangible values, such as Corporate Social Responsibility, can result in a good reputation